RC4 (Reading, Constructing, Collecting, Changing, Concluding) Learning Model to Enhance Students’ Scientific Literacy Skills: Is It Effective? - Fersty Isna Kusumawardani; Indrawati Indrawati; Pramudya Dwi Aristya Putra (Jurnal Pendidikan Edutama, 2023)
Abstract: This study aims to identify the level of effectiveness of the application of the RC4 learning model on students' scientific literacy skills in science learning at junior high school. The participants involved in the present research consisted of 30 students from 7B class at SMP Negeri 1 Jember, East Java, Indonesia. The current research employed One Group with Pre-Test and Post-Test Research Design. Two trial sessions on Environmental Pollution and the Solar System material were administered. Data obtained from students' scientific literacy tests were analyzed using the Normalize Gain (N-Gain) formulation. The average N-Gain value in the small group trial showed a result of 0.53 and in the large group trial, it showed a result of 0.54. It can be concluded that the level of effectiveness of applying the RC4 learning model to students' scientific literacy skills was in the moderate category. Keywords: Scientific literacy, learning model, natural science, junior high school.  Abstrak: Penelitian ini bertujuan mengidentifikasi tingkat keefektifan penerapan RC4 terhadap kemampuan literasi sains siswa pada pembelajaran IPA di SMP. Subjek pada penelitian ini terdiri dari 30 orang siswa kelas 7B di SMP Negeri 1 Jember, Jawa Timur, Indonesia. Desain penelitian yang digunakan adalah One Group with Pre-Test and Post-Test Research Design, dengan dua sesi uji coba pada materi Pencemaran Lingkungan dan Sistem Tata Surya. Kemudian data hasil literasi sains siswa dianalisis menggunakan formulasi Normalize Gain (N-Gain). Nilai rerata N-Gain pada uji coba kelompok kecil menunjukkan nilai sebesar 0,53 dan pada uji coba kelompok besar menunjukkan nilai sebesar 0.54. Kesimpulan hasil penelitian menunjukkan bahwa tingkat keefektifan penerapan model pembelajaran RC4 terhadap kemampuan literasi sains siswa termasuk dalam kategori keefektifan sedang. Keywords: literasi sains, model pembelajaran, ipa, sekolah menengah pertama.